1994
DOI: 10.2105/ajph.84.4.571
|View full text |Cite
|
Sign up to set email alerts
|

Using physician correspondence and postcard reminders to promote mammography use.

Abstract: OBJECTIVES. In a health maintenance organization that mails letters to women recommending that they schedule mammograms, we conducted a randomized trial to evaluate simple methods of increasing the use of screening mammography. METHODS. Using a 2 x 2 factorial design, we tested the effects of (1) mailing the recommendation letter from each woman's primary care physician rather than from the program director and (2) sending a subsequent reminder postcard. RESULTS. Sending a reminder postcard nearly doubled the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 21 publications
2
52
0
Order By: Relevance
“…Non-electronic reminders provided directly to patients have been shown to improve adherence to care guide- [9][10][11][12] . The use of a secure, interactive personal health record (PHR) tethered to an EHR can provide an avenue for patients to review and update health information 13 , and has the potential to improve adherence to guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Non-electronic reminders provided directly to patients have been shown to improve adherence to care guide- [9][10][11][12] . The use of a secure, interactive personal health record (PHR) tethered to an EHR can provide an avenue for patients to review and update health information 13 , and has the potential to improve adherence to guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Larson et al found that a personalized postcard from the physician improved influenza vaccination rates, 5 but Taplin et al found that mailing the recommendation from the woman's primary care physician rather than from the program director did not increase the likelihood that the patient would get a mammogram. 20 We hypothesized that both personalizing and tailoring the reminder using information easily accessible to us would enhance its effectiveness. This question was studied in a randomized, controlled trial of computer-generated, mailed reminders used to increase influenza vaccination rates in high-risk, adult patients in a large group practice.…”
mentioning
confidence: 99%
“…In the United States, mailed interventions have been tested extensively as a method to increase screening among patients of managed care organizations or large group practices (28,30,(41)(42)(43)(44)(45), but these studies are not directly comparable with the present study. Clinic-based studies typically have lists of women known to be eligible for the intervention because they are probably due for a mammogram and have all or part of their screening costs covered.…”
Section: Discussionmentioning
confidence: 76%
“…Direct mail provides a relatively efficient and inexpensive way (24) to reach many geographically dispersed individuals in their homes, including those not typically exposed to mass media (23,25). Although direct mail may not be an effective strategy for altering core attitudes and beliefs about health behaviors, mailed interventions can prompt behavior, enhance awareness, and reduce specific knowledge gaps (26)(27)(28)(29)(30). Finally, direct mail materials can be tailored to various target audiences, including older and low literacy populations (27,31).…”
Section: Introductionmentioning
confidence: 99%